2018
DOI: 10.1007/s10164-018-0551-2
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of personality between juveniles and adults in clonal gecko species

Abstract: The developmental perspectives of animal personality enhance our understanding of how personality structure changes in relation to life stage. Clonal animals are ideal models for developmental studies because personality differences can be solely attributed to environmental factors. Here, I investigated the presence of personality within a species of clonal gecko, Lepidodactylus lugubris, at different developmental stages. For juveniles and adult geckos, I measured exploration (reaction to a novel situation) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Substantial variation in specific behavioral measures, even in inbred lines raised in standardized conditions, has been observed in several clonal animals, including geckoes ( Sakai, 2018 ), amazonian mollies ( Bierbach et al, 2017 ), and aphids and nematodes ( Schuett et al, 2011 ; Stern et al, 2017 ). Genetic model systems hold particular promise for the mechanistic dissection of this variation, and intragenotypic variability (IGV) in behavior has been characterized in mice ( Freund et al, 2013 ), zebrafish ( Bierbach et al, 2017 ), and Drosophila .…”
Section: Introductionmentioning
confidence: 99%
“…Substantial variation in specific behavioral measures, even in inbred lines raised in standardized conditions, has been observed in several clonal animals, including geckoes ( Sakai, 2018 ), amazonian mollies ( Bierbach et al, 2017 ), and aphids and nematodes ( Schuett et al, 2011 ; Stern et al, 2017 ). Genetic model systems hold particular promise for the mechanistic dissection of this variation, and intragenotypic variability (IGV) in behavior has been characterized in mice ( Freund et al, 2013 ), zebrafish ( Bierbach et al, 2017 ), and Drosophila .…”
Section: Introductionmentioning
confidence: 99%
“…Findings from other studies have also countered the notion that behavioural differences among individuals are necessarily consistent over long timescales (Kanda et al 2012;Polverino et al 2016a;Sakai 2018;Rohrer and Ferkin 2020). For example, meadow voles (Microtus pennsylvanicus) were exposed to a novel object test, with the number of approaches towards the novel object (activity), latency to approach (exploration), and latency to move within the test arena (boldness) being measured six times every 60 days (Rohrer and Ferkin 2020).…”
Section: Temporal Stability In Behavioural Variationmentioning
confidence: 98%
“…The decrease in behavioural difference over time is thought to depend upon individuals progressing through different ontogenetic stages (Debeffe et al 2015;Wuez and Kruger 2015;Stamps and Krishnan 2017;Mitchell et al 2020). However, several longitudinal studies indicate that personality estimates can also increase with animals' age, revealing that behavioural differences are often more consistent later in life (Debeffe et al 2015;Polverino et al 2016aPolverino et al , 2016bSakai 2018;Rohrer and Ferkin 2020). If behavioural differences among individuals increase over a lifetime, behavioural syndromes might also be more pronounced in groups of older than young individuals (Polverino 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to complex patterns of social behavior, some studies have found that reptiles display personalities that change across ontogeny. For example, decreases in boldness and exploration across the transition from juvenile to adult were found in mourning geckos (Lepidodactylus lugubris; Sakai, 2018). In snakes, long-term individual consistency in predator defense behavior has been observed in Mexican black-bellied gartersnakes (Thamnophis melanogaster; Herzog & Burgardt 1988) and northwestern gartersnakes (Thamnophis ordinoides; Brodie, 1993;see Waters 2017 for review).…”
Section: Introductionmentioning
confidence: 99%